A STUDY ON THE ABILITY OF THE THIRD YEAR STUDENTS OF SMAN 1 PANGKALAN KURAS IN WRITING APPLICATION LETTER - Bulan Sawitri; Eliwarti Eliwarti; Novitri Novitri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research aims to find out the writing ability of the third year students of SMAN 1 Pangkalan Kuras. The population of this research is all the third year students of SMAN 1 Pangkalan Kuras. The number of sample is 60 students selected by using cluster random sampling technique. The instrument to collect the data was writing test and scored by three raters. The data were analyzed by classifying them into five levels of ability, such as very poor, poor, average, good, and excellent. Based on the findings of this research, it was found that the students’ writing ability was in good level with the average score 74.12. In conclusion the third year students of SMAN 1 Pangkalan Kuras have a good ability in writing application letter.Key Words: Writing’ Ability, Application Letter